Hubungan Dukungan Sosial dengan Kecemasan Sosial pada Klien Balai Pemasyarakatan Kelas I Banjarmasin - Nisa, Risa Latin; Fitriah, Aziza; Rifandi, Akhmad (Jurnal Psikologi Terapan, 2023)
This study aims to examine the relationship between social support and social anxiety among inmates at Bapas Kelas I Banjarmasin. A quantitative research design with a correlational approach was employed to investigate the potential connection between these variables. The sample comprised 128 inmates, selected using quota sampling, from the total population of 1,278 registered in the System Database Pemasyarakatan (SDP) of the institution. Data were collected using self-report measures: the Social Support Scale based on Sarafino and Smith's aspects of social support and the Social Anxiety Scale based on La Grace and Lopez's aspects of social anxiety. The collected data were analyzed using Pearson's product-moment correlation in SPSS version 22.0. The results revealed a statistically significant negative correlation between social support and social anxiety (r = -0.404, p < 0.001), indicating that higher levels of social support are associated with lower levels of social anxiety among inmates. The study also examined the distribution of social anxiety levels and found that 56% of participants exhibited low social anxiety, 42% had moderate social anxiety, and 2% experienced high social anxiety. Additionally, the analysis indicated that 80% of inmates reported high social support, while 20% reported moderate social support. The implications of these findings suggest the importance of fostering social support networks within correctional facilities to alleviate social anxiety among inmates. Providing mental health services, implementing gender-specific interventions, and focusing on rehabilitation and reintegration strategies are recommended to enhance inmates' overall well-being. Further research should explore the specific factors contributing to variations in social support and social anxiety levels among inmates. By addressing these aspects, correctional institutions can play a pivotal role in promoting inmates' psychological well-being and successful reintegration into society upon release.